Towards thermal noise free optomechanics. (17th October 2016) - Page, Michael A; Zhao, Chunnong; Blair, David G; Ju, Li; Ma, Yiqiu; Pan, Huang-Wei; Chao, Shiuh; Mitrofanov, Valery P; Sadeghian, Hamed
Abstract: Thermal noise generally greatly exceeds quantum noise in optomechanical devices unless the mechanical frequency is very high or the thermodynamic temperature is very low. This paper addresses the design concept for a novel optomechanical device capable of ultrahigh quality factors in the audio frequency band with negligible thermal noise. The proposed system consists of a minimally supported millimeter scale pendulum mounted in a double end-mirror sloshing cavity that is topologically equivalent to a membrane-in-the-middle cavity. The radiation pressure inside the high-finesse cavity allows for high optical stiffness, cancellation of terms which lead to unwanted negative damping and suppression of quantum radiation pressure noise. We solve the optical spring dynamics of the system using the Hamiltonian, find the noise spectral density and show that stable optical trapping is possible. We also assess various loss mechanisms, one of the most important being the acceleration loss due to the optical spring. We show that practical devices, starting from a centre-of-mass pendulum frequency of 0.1 Hz, could achieve a maximum quality factor of (10 14 ) with optical spring stiffened frequency 1–10 kHz. Small resonators of mass 1 ( μ ) g or less could achieve a Q -factor of (10 11 ) at a frequency of 100 kHz. Applications for such devices include white light cavities for improvement of gravitational wave detectors, or sensors able to operate near the quantum limit.